2005
DOI: 10.1111/j.1365-2567.2004.02114.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐linking of neutrophil CD11b results in rapid cell surface expression of molecules required for antigen presentation and T‐cell activation

Abstract: Summary Recent studies suggest that neutrophils may play a role in antigen presentation. In support of this hypothesis it has been shown that these cells appear to contain cytoplasmic stores of molecules required for this function, i.e. major histocompatibility complex class II (DR) antigen, CD80 and CD86. In this study we have considered a mechanism for the translocation of these preformed molecules onto the cell surface which does not require active synthesis. Cross‐linking of the Mac‐1 molecule (CD18 + CD11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 39 publications
4
48
1
3
Order By: Relevance
“…In a pregnant mouse model with C. psittaci serotype І infection and an anti-neutrophil MoAb (RB6-8C5), the lack of neutrophils led to a substantial decrease in the number of macrophages and T lymphocytes in the liver of mice (6). Indeed, using confocal microscopy and immunoelectron microscopy Gavin P, et al provided evidences that CD80, CD86 and MHC class II antigen are colocalized within neutrophil secretory vesicles, and the cross-linking of neutrophils CD11b was required for the translocation of these molecules from pre-existing cytoplasmic stores onto the cell surface (31). Therefore, during the late stage of infection, the down-regulation of CD11b expression on neutrophils in C3H mice might attenuate the antigen-presenting function of neutrophils, which may be another mechanism of the high susceptibility of C3H mice to C. trachomatis infection.…”
Section: Discussionmentioning
confidence: 99%
“…In a pregnant mouse model with C. psittaci serotype І infection and an anti-neutrophil MoAb (RB6-8C5), the lack of neutrophils led to a substantial decrease in the number of macrophages and T lymphocytes in the liver of mice (6). Indeed, using confocal microscopy and immunoelectron microscopy Gavin P, et al provided evidences that CD80, CD86 and MHC class II antigen are colocalized within neutrophil secretory vesicles, and the cross-linking of neutrophils CD11b was required for the translocation of these molecules from pre-existing cytoplasmic stores onto the cell surface (31). Therefore, during the late stage of infection, the down-regulation of CD11b expression on neutrophils in C3H mice might attenuate the antigen-presenting function of neutrophils, which may be another mechanism of the high susceptibility of C3H mice to C. trachomatis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are among the first cells to respond to inflammation, and circulating platelets help them in this endeavor, first by self-activation, then by mediating integrin expression on the neutrophil surface through release of P-selectin from alpha granules and adenosine tri-and diphosphate from dense bodies 18) . Besides antibacterial activity, Mac-1 integrin molecules mediate antigen presentation and/or T-cell activation 19) . Overexpression of CD11b/CD18 on leukocyte surfaces in ragpickers, therefore, possibly underscores stimulation of immune defense to combat pathogenic microorganisms in their working environment 16) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these cells have a more elaborate role in the innate defense against pathogens. Both in vitro and in vivo studies have shown that neutrophils are capable of Ag presentation by MHC class II complexes (5)(6)(7) and are able to express the costimulatory molecules CD80 and CD86 (8), which are relevant for induction of T cell proliferation (5, 7). Activated neutrophils have been shown to secrete cytokines such as IL-1, IL-1Ra, IL-6, IL-8, IL-12, IL-10, TNF-a, IFN-g, and PGE 2 (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%